Comparative impact of a single application of selected broad spectrum herbicides on ecological components of oil palm plantation - Wibawa, Wahyu; Mohamad, Rosli; Omar, Dzolkhifli; Mohd. Zain, Nurmasirah; Puteh, Adam; Awang, Yahya (Academic Journals, 2010)
Proper choice and use of herbicides are important for the effective control of weed and environmental safety. Herbicides which possess both characteristics are preferred for use in weed control operation. A study was, therefore, conducted to compare the performance of common broad-spectrum herbicides of paraquat, glyphosate and glufosinate-ammonium to control weeds and their impact to the surrounding ecological components of an oil palm plantation. Field experiments set up in the oil palm plantation were sprayed accordingly with recommended rates of the herbicides (paraquat, 600 g a.i. ha-1; glufosinate-ammonium, 600 g a.i. ha-1 and glyphosate, 1200 g a.i. ha-1) at 200 L ha-1, using knapsack sprayer fitted with a 2.5 deflector nozzle. Untreated control plots were included in the experiment. The effectiveness of the herbicides on weed population, their residues in the soil and indirect effects on oil palm crop plants were evaluated. Paraquat killed 74% of the weed population with effective control period of 8.8 WAT, whereas, both glyphosate and glufosinate-ammonium caused maximum killed of 99% and remained effective until 14.8 WAT. The measurements of weed dry weight and growth reduction also indicated that the herbicides caused significant reduction compared with the control, but paraquat was comparatively less effective than glyphosate and glufosinate-ammonium. Minimal and insignificant residue levels of the herbicides were detected in the soil after application which caused no significant detrimental effect on oil palm crop development and production, or the microorganism populations (fungi and bacteria) in the soil. The study indicated that the use of the herbicides can be effective in controlling the mixed weed population in oil palm plantation; glyphosate and glufosinate-ammonium showed greater effectiveness than paraquat. The herbicides, applied at their recommended rates, left no residual effects on the surrounding ecological components of oil palm plantation.